Dose–response relationship of dietary Omega-3 fatty acids on slowing phenotypic age acceleration: a cross-sectional study - Wu, Dongzhe; Jia, Yishuai; Liu, Yujia; Shang, Mingyu (Frontiers in Nutrition, 2024)
Purpose: This study investigates the association between dietary Omega-3 fatty acid intake and accelerated phenotypic aging, referred to as PhenoAgeAccel. PhenoAgeAccel is defined as the difference between phenotypic biological age, calculated using blood biochemical markers, and chronological age. This study assesses the potential of Omega-3 intake to slow biological aging and its implications for public health.Methods: Utilizing data from the NHANES from 1999 to 2018, this cross-sectional study included 20,337 adult participants. Through a nationally representative sample combined with comprehensive phenotypic age calculation methods, a cross-sectional analysis of Omega-3 fatty acid intake and accelerated phenotypic aging was conducted. Weighted generalized linear regression models and restricted cubic spline analyses were applied to explore the potential non-linear relationships between them. Threshold effects were further clarified through piecewise regression models, and the impact of different demographic and health characteristics was evaluated through interaction effect tests. Results: After adjusting for various potential confounding factors, a significant negative correlation was found between Omega-3 fatty acid intake and PhenoAgeAccel (β = -0.071; 95%CI: -0.119, -0.024; P = 0.004), indicating that an increase in Omega-3 intake is associated with a slowdown in PhenoAgeAccel. Specifically, for each unit increase in Omega-3 intake, the accelerated phenotypic aging decreased by an average of 0.071 units, revealing a significant linear negative correlation between Omega-3 intake and PhenoAgeAccel. Moreover, threshold effect analysis identified an Omega-3 fatty acid intake threshold (1.103 grams/day), beyond which the impact of Omega-3 intake on accelerated phenotypic aging tends to stabilize. Additionally, factors such as gender, age, race, and hypertension may influence the relationship between Omega-3 intake and PhenoAgeAccel, suggesting individual dietary guidance needs in different populations.This study highlights the potential role of dietary Omega-3 fatty acids in regulating PhenoAgeAccel and supports the strategy of delaying the aging process through dietary interventions to increase Omega-3 intake. The findings of this study contributes to the development of precise nutritional intervention strategies for different populations to optimize healthy longevity.